CASE STUDY OF HYSTERECTOMY ET CAUSA MYOMA UTERY WITH PHYSIOTHERAPY MANAGEMENT - Yustitya Aprila Nur Fadilah; W Wahyuni; Nurul Muflihah (CV. Fahr Publishing, 2026)
Hysterectomy is a major gynecological surgical procedure commonly performed in cases of uterine myoma and may lead to various postoperative problems, such as pain, decreased muscle strength, limited mobility, and impaired functional activities. These conditions can negatively affect patients’ quality of life if not managed properly. Physiotherapy plays an important role in accelerating recovery and preventing complications due to postoperative immobilization. This case report aims to describe the physiotherapy management of a patient following total hysterectomy with bilateral salpingo-oophorectomy due to uterine myoma. The method used was a case study of a 59-year-old female patient who complained of postoperative wound pain, abdominal muscle tightness, and limitations in functional activities. Physiotherapy interventions were provided in three sessions, including pelvic floor exercises, deep breathing exercises, bed mobility (right and left side-lying), active exercises for upper and lower extremities, range of motion exercises, transfer training, and early ambulation. Evaluation was conducted using the Numeric Rating Scale (NRS) for pain, Manual Muscle Testing (MMT) for muscle strength, and the Kenny Self Care Index for functional activities. The results showed a significant reduction in pain, improvement in pelvic muscle strength, and increased functional ability from total dependence to full independence. Physiotherapy interventions are effective in supporting functional recovery and improving the quality of life of patients following hysterectomy.